A novel EVA composite with simultaneous flame retardation and ceramifiable capacity. Issue 63 (10th July 2015) - Di, Hong-Wei; Deng, Cong; Li, Rui-Min; Dong, Liang-Ping; Wang, Yu-Zhong
<x xml:space="preserve">Abstract</x> Ethylene-vinyl acetate (EVA) filled with glass dust (GD), glass fiber (GF), OMMT, and melamine cyanurate (MCA) was developed as a ceramifiable flame-retardant polymer composite for cables and insulated wires.